Dysregulated lncRNA-miRNA-mRNA Network Reveals Patient Survival-Associated Modules and RNA Binding Proteins in Invasive Breast Carcinoma - Dong, Yu; Xiao, Yang; Shi, Qihui; Jiang, Chunjie (Frontiers in Genetics, 2020)
Breast cancer is the most common cancer in women, but few biomarkers are effective in clinic. Previous studies showed the important roles of non-coding RNAs in diagnosis, prognosis and therapy selection of breast cancer, and suggested the significance of integrating molecules at different levels for interpreting the mechanism of breast cancer. Here we collected transcriptome data including long non-coding RNA (lncRNA), microRNA (miRNA) and mRNA of ~1,200 samples including 1079 invasive breast carcinoma samples, as well as 104 normal samples from The Cancer Genome Atlas (TCGA) project. We identified differentially expressed lncRNAs, miRNAs and mRNAs that were able to distinguish invasive carcinoma samples from normal samples. We further constructed an integrated dysregulated network consisting of differentially expressed lncRNAs, miRNAs and mRNAs, and found housekeeping and cancer related functions. Besides, 58 RNA binding proteins (RBPs) involving in biological processes that are essential to maintain cell survival were found in the dysregulated network, and 10 were correlated with overall survival. In addition, we identified two modules to stratify patients into high- and low-risk subgroups. The expression patterns of these two modules were significantly different between invasive carcinoma and normal samples, and some molecules were high confident biomarkers in breast cancer. Together, these data demonstrated an important clinical application in improving outcome prediction for invasive breast cancers.